Design of a hydro-electric power plant - Elsas, Marshal; Hubbard, Harvey B.; Cooley, Jerome Earl (My University, 1907)
Introduction: In determing the feasibility of utilizing Water-power to operate electrically the industries of any city, many things must necessarly be taken in to careful consideration. Among which are; the amount of water-power available. Cost of developing this power. The interest on this amount. Demands for power. Comparsion of water power with that of steam with respect to cost. All of these and many others seemingly non-important items must be taken in to consideration in order that the financial out-come of such an investment as a water power plant may be determined. Charles. T. Main makes the following statement as to the value of Water-power. " The value of an undeveloped variable power is usually nothing if the varation is great, unless it is to be supplemented by a steam-plant. It is of value then only when the cost per horse power for the double plant, is less than the cost for steam- power under the same conditions as mentioned for a permanent power. And its value can be represented in the same manner, as the value of a permanent power has been represented. The value of a developed power, is as follows:- If the power can be run cheaper than steam, the value is that of the power plus the cost of the plant less depreciation, if it can not be run as cheaply as steam considering its cost,etc, the value of the power is nothing, but the value of the plant is such as could be paid for if new, which would bring the total cost of runing down to the cost of steam power, less depreciation.” Mr. Main's comparison has been criticised by a great many because it is in favor of a steam plant, which in reality…
Citation: Elsas, Marshal, Hubbard, Harvey B., and Cooley, Jerome Earl. Design of a hydro-electric power plant. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Hydroelectric Power Plants; Designing Power Plants; The Economics of Power Plants; Theses